Clinical and pathological characteristics of patients with pulmonary inflammatory pseudotumors: An 18-year retrospective study of 31 cases. Issue 35 (3rd September 2021) - Chen, Heng-Chi; Fu, Qiang; Song, Yan; Wang, Da-Li
Abstract : Abstract: To investigate the clinical and pathological characteristics in patients with pulmonary inflammatory pseudotumors (PIP). This retrospective study included 31 patients with PIP from 2001 to 2019. Preoperative computed tomography scan was performed in all patients. Clinical and pathological characteristics were collected and analyzed. Thirty-one patients (16 female and 15 male) were recruited, with a median age of 57 years (range, 11–72 years). Eight (25.8%) patients were asymptomatic, and the others had symptoms characterized by cough with sputum, chest and back pain, dry cough, fever and blood in sputum, or hemoptysis. All cases were single lesions, including 23 cases in the right lung, and 8 cases in the left lung. Computed tomography scan demonstrated irregular lobulated nodules or masses in 14 patients, and regular round or oval nodules or masses in 11 cases. The blurred edge of tumors and spiculation was found in 12 cases. Microscopic results were characterized by the collection of inflammatory mesenchymal cells. Immunohistochemical examination showed vimentin, smooth muscle actin, and anaplastic lymphoma kinase positive. Complete tumor resection was obtained in all cases. No recurrence or metastasis was observed during the follow-up period. PIP has a variety of manifestations. Preoperative diagnosis is difficult to reach. The final diagnosis still depends on the pathological and immunohistochemical examination. Complete surgical resection is the main treatment at present, and the overall prognosis is good.